Case Study: Catracha Coffee, a Replicable Business Model? - Patt C., Suleima Y. (Zamorano: Escuela Agrícola Panamericana, 2022, 2022)
The emergence of income- generating activities for nonprofit organizations has created a new approach to the operating business model concept. This approach entails the combination of characteristics and values that focus on the bottom line of making a business model incomegenerating, while still integrating the three pillars of sustainability within its core. The purpose of this document is to create a case study as a teaching tool of the Department of Agribusiness Administration of Zamorano and for other business schools in the region, in the discipline of social enterprise. A case study is based on real-life management issues. The intention is to put the learner in the shoes of the decision maker by placing them in the chronological context of the business so that learner may make a judgment based on the facts it has and the uncertainties that exist within the business. The present case study was created based on the analysis of a business model operating in Santa Elena, La Paz dedicated to the international commercialization of specialty coffee with focus on community development and sustainability. It was developed based on a mixed analysis of quantitative and qualitative data of the business model to have a better understanding of the operations of this business model, and thus be able to make a deductive inference of what are the advantages and limitations of operating a similar business model. On the other hand, this analysis has the purpose of demonstrating with the collected data whether the business model is replicable or not through the writing of the case study along with its teaching note